PERILAKU KECURANGAN AKADEMIK MAHASISWA AKUNTANSI: DIMENSI FRAUD TRIANGLE - Annisa Fitriana; Zaki Baridwan (Universitas Brawijaya, 2012)
Abstract: Academic Fraud Behaviour of Accountinng Students: Fraud Triangle Dimension. This study examine the dimensions of Fraud Triangle to explain this effect on the student’s cheating. This study uses a model of research The Academic Dishonesty Scale modifi cation. Sample in this study were 217 accounting students in Brawijaya University Malang. Data was collected through survey methods. This study have obtained empirical evidence that student’s cheating behaviorwas determined by the dimensions of the Fraud Triangle consists of incentive, opportunity and rationalization. Abstrak: Perilaku Kecurangan Akademik Mahasiswa Akuntansi: Dimensi Fraud Triangle. Studi ini menguji dimensi Fraud Triangle untuk menjelaskan perilaku kecurangan akademik mahasiswa dengan menggunakan model The Academic Dishonesty Scale modifi cation.Sampel penelitian adalah 217 mahasiswa akuntansi Universitas Brawijaya Malang. Data dikumpulkan dengan metoda survei. Hasil penelitian memperoleh bukti empiris bahwa perilaku kecurangan mahasiswa ditentukan oleh dimensi Fraud Triangle yaitu tekanan, peluang dan rasionalisasi.